שלמה גרודזנסקי: הצועני ושורשיו העמוקים - זנדבנק, שמעון (מכאן, 2020)
Following Marianne Moore's Poetry, Grodzensky's position as critic can be describes as humanistic rather than literary or formalistic. The human being behind the text is what really matters and is judjed by standards adopted from English and American critism. Side by side with literary criteria borrowed from the likes of Eliot or Leavis, the Jewish tradition and authentic Judaism paly a central part in his personal canon of Modern Hebrew literature, which includes Brenner and Shofman alongside neglected poets such as Lensky or Noah Stern. Gershon Scholem, in his obituary of Grodzensky, calls him "a gypsy with deep roots", combining an openness to world literature and philosophy with profound Jewish rootedness.